Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Identifying and understanding mechanisms in an inhibitory control training in patients with binge-eating-disorder – an exploratory analysis - Sebastian M. Max; Katrin E. Giel; Christian Plewnia; Veronika Lossa; Stephan Zipfel; Kathrin Schag (Appetite, 2025)

Metal ratios as possible biomarkers for amyotrophic lateral sclerosis - Lassi Koski; Elina Berntsson; Max Vikström; Sebastian K.T.S. Wärmländer; Per M. Roos (Journal of Trace Elements in Medicine and Biology, 2023)

Mind the food: behavioural characteristics and imaging signatures of the specific handling of food objects - Sebastian M. Max; Philipp A. Schroeder; Jens Blechert; Katrin E. Giel; Ann-Christine Ehlis; Christian Plewnia (Brain Structure and Function, 2021)
In our world with nearly omnipresent availability of attractive and palatable high-calorie food, the struggle against overweight and obesity is a major individual and public health challenge. Preference for unhealthy food and eating-related habits have a strong influence on health, suggesting that high-calorie food triggers fast and near-automatic reaching and grasping movements. Therefore, it is important to better understand the specific neural mechanisms that control the handling of food involving a coordinated interplay between sensoric, motoric, and cognitive subsystems. To this end, 30 healthy participants (Ø BMI: 22.86 kg/m 2 ; BMI range: 19–30 kg/m 2 ; 23 females) were instructed to collect one of two concurrently presented objects (food vs. office tools) by manual movement in virtual reality (VR) and on a touchscreen. Parallel to the task in VR, regional brain activity was measured by functional near-infrared spectroscopy (fNIRS). In the VR and on the touchscreen, stimulus recognition and selection were faster for food than for office tools. Yet, food was collected more slowly than office tools when measured in VR. On the background of increased brain activity in the right dorsolateral prefrontal cortex (dlPFC) during food trials, this suggests more behavioural control activity during handling foods. In sum, this study emphasizes the role of the right dlPFC in faster recognition and selection of food as part of a food-valuation network, more controlled handling of food in the VR which highlights the relevance of medium for modelling food-specific embodied cognitions.